Coping with chronic periprosthetic joint infection after failed revision of total knee and hip arthroplasty: a qualitative study on patient's experiences in treatment and healing. - Vincent Tilo Krenn; Maria Sarah Bönigk; Andrej Trampuz; Martin Liebisch; Carsten Perka; Sebastian Meller (PLoS ONE)
Periprosthetic joint infections (PJI), along with the extensive medical and surgical interventions required for treatment, impose a substantial psychological burden on patients. Given the need for patients to adapt to long-term physical limitations and ongoing medical challenges, this qualitative study aims to explore the nature of psychological coping amongst patients with chronic cases of PJI. A total of 18 patients (8 men and 10 women, aged 55 to 92) who underwent a total knee or hip arthroplasty revision due to chronic PJI were recruited at a single academic institution between August 2022 and July 2023. Semi-structured interviews were conducted at two timepoints and analyzed using thematic analysis. We identified the nature of coping with PJI as patients' process-orientation towards healing. This encapsulates constant adaptation to challenges and losses in day-to-day life, managing expectations and proactively developing a sense of self-efficacy during treatment and healing. Patients expressed uncertainty and unpredictability to treatment trajectories and getting a feeling of being stuck, where health and well-being oscillates between progression and regression. These experiences contributed to unstable relationships with healthcare practitioners which were influenced by loss of trust and perceived treatment failures. A holistic view on patients, taking them seriously in their concerns and providing clear information were identified as crucial factors in shaping a positive patient-physician relationship. Acknowledging the fluctuating nature of chronic PJI treatment, physicians should adopt a process-oriented approach that promotes step-by-step healing while maintaining a positive patient-physician relationship. Recognizing the profound psychological impact, we propose the establishment of a new subdiscipline, namely 'Psycho-Endoprosthetics', to facilitate interdisciplinary collaborations for research and practice in septic surgery.